Pengembangan Konsep Cleaner Drilling Berdasarkan Studi Kasus Pengeboran Minyak Di Perusahaan “XXX” Menggunakan Pendekatan FMEA - Haryono Haryono; samsudin affandi; Gatot Subroto (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2022)
ABSTRACT In the oil and gas industry, from planning to drilling to closing oil fields, it has the potential to cause impacts and needs to be addressed. One of the efforts to handle the impact proposed the concept of "Cleaner Drilling". The Cleaner Drilling is based on changing the mindset that originally considered impacts and waste as a threat to the environment, turned into profitable opportunities, used for other activities. The purpose of this study is to determine and develop the concept of Cleaner Drilling and the FMEA method, so that the value of the results obtained after the Medial Action is carried out will be known. The scope of this research is divided into two studies, namely the study of secondary data and the study of FMEA. The scope of the study is divided into two aspects, namely environmental aspects and technological aspects. After this research was carried out, it was obtained that, in its implementation the Cleaner Drilling concept determined to implement the "Warning and Reporting System" concept which could provide "Commend and Control" to the emerging markers, so as to avoid the occurrence of failures and losses in the oil and gas process.